DATA UPDATES IN THE EFFICIENCY MEASUREMENT OF COOPERATIVES IN INDONESIA - Abi Pratiwa Siregar; Jamhari Jamhari; Lestari Rahayu Waluyati (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2020)
Updating data is an absolute thing to do to produce a decision or make a valid and reliable policy. In the field of co-operatives, data updated from time to time can be utilized to measure the extent to which cooperatives use available resources to achieve predetermined outputs. The objectives of this study are: 1) to find out the application of co-operative data updates in Indonesia, and 2) to measure the efficiency of co-operatives in Indonesia. The method used is a descriptive analysis using secondary data from the Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia's (Kemenkop dan UKM) publication. The results showed that the data update of co-operatives in Indonesia has been running regularly. However, in several published publications,  the status is very temporary and have not been updated with the most recent time. Furthermore, based on efficiency aspects, co-operatives in several regions have not run their activities efficiently, either the activities that have not been optimal) or activities have exceeded the optimal capacity.